Upcycling of natural fibers to create new fashion products - Marques, António Dinis (2021)
This paper aims to discuss how to give a new life to textile waste, creating new products and thus extending the life cycle of natural fibers. Also it is intended to create a sustainable fashion brand that is based on circular economy principles and on the upcycling of natural fiber fabrics at the end of life, for the creation of clothing and accessories. The raw materials for this project of upcycling will be industrial pre consumption waste, such as production surplus, leftovers, scraps and fabric samples that are discarded by companies. Preference will be given to natural fibers such as cotton and linen.